MEMBANGUN MODERASI BERAGAMA UMAT MELALUI BUDAYA RELIGIUS SEKOLAH - Ni Ketut Erna Muliastrini; Putu Bayu Ariska Putra Gotama; Ni Nyoman Lisna Handayani (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
The purpose of this research is to build, strengthen, and become the foundation of behavior, traditions, and daily habits at school. This study uses a qualitative research approach with data collection techniques using the literature review method. The analysis of the model in building religious moderation of the people through the religious culture of the school uses the approach of moral knowing, moral feeling, and moral action. The results show that through the creation of a religious atmosphere/culture, exemplary, and habituation will be able to build a moderate learning community.Keywords: Religious Culture, Religious Moderation, School